2019
DOI: 10.3390/admsci9010021
|View full text |Cite
|
Sign up to set email alerts
|

Land Governance Re-Arrangements: The One-Country One-System (OCOS) Versus One-Country Two-System (OCTS) Approach

Abstract: This paper evaluates how land governance is re-arranged in a state re-structuring process. We compare the cases of the (re-)unification of China with Hong Kong with that of West and East Germany. The division and (re-)unification of these states mark different land governance re-arrangements. The China-Hong Kong (re-)unification relied on a one-country two-system (OCTS) approach, while in West and East Germany, (re-)unification resulted in the creation of a one-country one-system (OCOS). Our key interest is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Many studies using EO data for North Korea have been proposed for monitoring land use and land cover Gathering and establishing reliable information for policy-making in pursuing Korean (re-)unification is more significant than ever during a peace-building process. In this process, re-shaping land governance are a fundamental question focusing on land tenure security, transferability, legitimacy and identity in (re-)unification setting [43,44]. Despite the passive attitude of the North Korean government to disclose information, it is possible to obtain data in a direct or indirect manner, such as [45]: official government reports (e.g., Korean Central News Agency: KCNA and Rodong Sinmun); materials from international organizations dealing with humanitarian aid (e.g., FAO, UNDP, UNFPA, WFP, WHO, UNICEF (For the resources, [46] etc.…”
Section: A Difficult-to-access Region: North Korea In the Contexts Ofmentioning
confidence: 99%
“…Many studies using EO data for North Korea have been proposed for monitoring land use and land cover Gathering and establishing reliable information for policy-making in pursuing Korean (re-)unification is more significant than ever during a peace-building process. In this process, re-shaping land governance are a fundamental question focusing on land tenure security, transferability, legitimacy and identity in (re-)unification setting [43,44]. Despite the passive attitude of the North Korean government to disclose information, it is possible to obtain data in a direct or indirect manner, such as [45]: official government reports (e.g., Korean Central News Agency: KCNA and Rodong Sinmun); materials from international organizations dealing with humanitarian aid (e.g., FAO, UNDP, UNFPA, WFP, WHO, UNICEF (For the resources, [46] etc.…”
Section: A Difficult-to-access Region: North Korea In the Contexts Ofmentioning
confidence: 99%
“…We used the purposive sampling technique to choose our respondents (small-scale farmers, customary authorities, registered surveying firms and local government authorities) based on their respective activities, experiences, knowledge and obligation in land administration and management. We applied the snowball sampling technique to make sure that the right small-scale farmers who were involved in land-use planning, regularization and formalization, and the government authorities who facilitated the approval of local plan at the local level were chosen [7,57].…”
Section: Methodsmentioning
confidence: 99%
“…This resulted in some families losing their land to the chiefs [26,34,56]. The chiefs were granted supervisory, jurisdictional, and territorial control of the people, land, and related natural resources in Talenteng on behalf of the colonial government [27,35,57]. The commissioner made the chiefs more business-orientated to increase their efficiency and effectiveness [26,56].…”
Section: Multiple Customary Authorities In Land Administration and Management In Talensimentioning
confidence: 99%
“…We also view land management as a combination of interventions in governance, based on questions of how and under what conditions such land interventions are responsible and how these can be supported by technologies. It is possible, therefore, that GIA supports both smart and responsible land management [70,71], especially of difficult-to-access regions where unknown or unsupported land governance exists [21,39,40].…”
Section: Geospatially Informed Analysis (Gia)mentioning
confidence: 99%
“…To date, however, there is a notable paucity of evidence-based literature describing and investigating how to identify unknown land tenure relations in North Korea due to the obvious difficulties in obtaining and analyzing empirical data. Several ways of overcoming these barriers to capturing the relationship between land tenure and governance and Korean (re-)unification process have recently been suggested that involve understanding and suggesting methods and solutions to problems [21,39,40]. Drawing upon both land administrative and geospatial engineering approaches, these enabled to provide reasonably consistent evidence and knowledge-base of an association between land tenure/land governance and (re-)unification of which relatively little is known.…”
Section: Introductionmentioning
confidence: 99%